IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH PAMEKASAN NOMER 22 TAHUN 2013 TENTANG PENATAAN PASAR TRADISIONAL, PUSAT PERBELANJAAN, DAN TOKO MODERN DI PASAR KOLPAJUNG PAMEKASAN JAWA TIMUR - Mohammad Bustanol Husein; Hany Novandina Maharani Sy; Rina Nur Azizah; Nur Fathin Luaylik (Journal Publicuho, 2023)
The purpose of this study was to find out the Implementation of District Regulation No. 22 of 2013 concerning Traditional Arrangements, Shopping Centers and Modern Stores at the Kolpajung Pamekasan Market. The method used in this research is a qualitative descriptive method, the case study of which was conducted at the Kolpajung Market, Pamekasan Regency. This research is focused on Government Policy in structuring Traditional Markets in Kolpajung Market to create a People's Market whose arrangement is in accordance with Regional Regulations. Primary data obtained by conducting interviews with four informants in accordance with the interview guide. The results of the study show that the traditional market arrangement for the Kolpajung market is still not in accordance with regional regulations, so market management is still not good enough.